Polychaeta (Annelida) associated with Thalassia testudinum in the northeastern coastal waters of Venezuela - Ildefonso Liñero Arana; Oscar Díaz Díaz (Revista de Biología Tropical, 2006)
Seasonal variations of polychaetes in a Thalassia testudinum bed were studied from June 2000 to April 2001 in Chacopata, northeastern Venezuela. Eight replicate samples were taken monthly with a 15 cm diameter core and the sediment was passed through a 0.5 mm mesh sieve. A total of 1 013 specimens, belonging to 35 species, was collected. The monthly density ranged from 387 ind/m² (September) to 1 735 ind/m² in May ( = 989±449 ind/m²). Species richness was lowest in August and September (8) and highest (25) in April ( = 18.00±5.29). The shoot density of Thalassia showed an average of 284±77.60 shoots/m², with extreme values in February (164) and May (422). Species diversity ranged from 1.25 in August and 3.33 bits/ind in December ( = 2.47±0.64). Significant positive correlations were detected among the number of Thalassia shoots, polychaete abundance and species richness, as well as among species richness, polychaete abundance and species diversity. Species number and average density were found within the intervals of mean values reported in similar studies. The higher number of species and organisms obtained in March-April and June-July can be attributed to the recruitment correlated with the regional up-welling. Rev. Biol. Trop. 54 (3): 971-978. Epub 2006 Sept. 29.